Ethiopia Groundwater Games for Resource Governance - International Food Policy Research Institute; Haramya University (International Food Policy Research Institute, 2023)
The study intervention included playing an irrigation groundwater governance game with multiple rounds and treatments in each village: one game with 5 men players and one game with 5 women players. Player choices and group outcomes (including water withdrawals and availability) for each round of the game were recorded and uploaded to SurveyCTO. A pre- and post-game survey of individual players immediately before and immediately after the game was conducted to gather data on characteristics of the players, their households and farms including current irrigation practices, individual mental models regarding groundwater resources and their management, and perceptions about levels of trust and cooperation between community members. The games and surveys were conducted in 15 treatment villages in the SNNP region of Ethiopia. Our sampling frame included 39 kebeles in 4 woredas, from which we drew a random proportional sample of kebeles from each woreda, resulting in 34 kebeles. We then randomly sorted the 34 kebeles into 17 treatment and 17 control kebeles. The last two kebeles in each group were reserved as replacements, and our main pilot sample consisted of 15 treatment and 15 control kebeles. The quantitative data is available for treatment communities only.